Improving current efficiency in low-temperature aluminum electrolysis with vertical inert electrodes - Caroline Mary Medino 1994- (2019)
Primary aluminum production is an energy intensive process with an average electric power consumption between 13 – 14 MWh per tonne of aluminum from the electrolysis process alone. Additional energy consumed in the aluminum plant is derived from the carbon anodes used in the process, equating to 3.8 MWh/t Al and contributing to 1.5 tonnes of carbon dioxide emissions for every tonne of aluminum produced. Most aluminum produced today is derived from non-renewable resources, with the aluminum industry emitting approximately 500 million tonnes of carbon dioxide equivalent annually; this constitutes about 1 % of the world’s total CO2 emissions. Countries like Iceland, Norway and Canada use hydroelectric and geothermal power for aluminum production so the only way to achieve substantial reduction in carbon dioxide emissions are to change the anode material. By replacing the carbon-based material with an inert material, oxygen, rather than carbon dioxide, is evolved as the main by-product. Potential materials for inert electrodes have a limited lifetime in the corrosive cryolite electrolyte at 960 °C. This drawback has led to significant research in altering electrolyte composition and lowering bath/electrolyte temperature to improve inert anode stability. The objective of this thesis was to investigate the influence that different operating parameters have on current efficiency in low temperature electrolysis with vertical inert electrodes. Primary aluminum production is an energy intensive process with an average electric power consumption between 13 – 14 MWh per tonne of aluminum from the electrolysis process alone. Additional energy consumed in the aluminum plant is derived from the carbon anodes used in the process, equating to 3.8 MWh/t Al and contributing to 1.5 tonnes of carbon dioxide emissions for every tonne of aluminum produced. Most aluminum produced today is derived from non-renewable resources, with the aluminum industry emitting approximately 500 million tonnes of carbon dioxide equivalent annually; ...